2009
DOI: 10.5194/acp-9-39-2009
|View full text |Cite
|
Sign up to set email alerts
|

Modeled and observed ozone sensitivity to mobile-source emissions in Mexico City

Abstract: Abstract. The emission characteristics of mobile sources in the Mexico City Metropolitan Area (MCMA) have changed significantly over the past few decades in response to emission control policies, advancements in vehicle technologies and improvements in fuel quality, among others. Along with these changes, concurrent non-linear changes in photochemical levels and criteria pollutants have been observed, providing a unique opportunity to understand the effects of perturbations of mobile emission levels on the pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Results from Zavala et al (2009) suggest that CO and VOC emissions from mobile sources decreased by approximately 40% over this time period while NO x emissions remained unchanged. Marley et al (2007) also reported evidence of a significant decrease in emissions of light olefins based on changes in ambient PAN concentrations.…”
Section: Implications For Ozone-precursor Sensitivitymentioning
confidence: 93%
“…Results from Zavala et al (2009) suggest that CO and VOC emissions from mobile sources decreased by approximately 40% over this time period while NO x emissions remained unchanged. Marley et al (2007) also reported evidence of a significant decrease in emissions of light olefins based on changes in ambient PAN concentrations.…”
Section: Implications For Ozone-precursor Sensitivitymentioning
confidence: 93%
“…Long-term analysis of ambient pollutants (Stephens et al, 2008;Zavala et al, 2009b) and Fig. 1 in this work indicate that despite the impressive 75% increase of the vehicle fleet over the 2000-2006 period, the ambient concentrations of CO and NO x have not increased proportionally.…”
Section: Impact Of Older High Emission Vehiclesmentioning
confidence: 98%
“…In particular, several modeling studies have been conducted in the past to understand the O 3 -NOx-VOC relationship that exists at several locations of its airshed at different times using CTMs. Even though there has been some controversy in the chemical regimes that these studies suggest for Mexico City (Torres-Jardón et al, 2009), recent studies that have applied CTMs conclude that this megacity is likely VOC-sensitive (Lei et al, 2007;Tie et al, 2007;Zavala et al, 2009;Song et al, 2010). However, Stephens et al (2008), following an observational-based approach, suggest that during working days the regime is NOx-sensitive, while during the week-ends a VOC-sensitive regime exists (which has grown stronger in the last decade).…”
Section: Introductionmentioning
confidence: 96%